Fertility dynamics in Russia: assessment and forecast - D. K. Sopov (Вестник университета)
Fertility rate is one of the key statistical indicators that needs to be tracked, analyzed in order to assess the current situation in the country and identify relevant trends as objectively as possible. The article analyzes the birth rate in Russia in recent years in the context of a 6-year period and identifies a trend in changing indicators of this phenomenon for subsequent years. In the course of the study, the author uses various statistical methods, such as horizontal analysis, the method of analytical alignment of the dynamic’s series and trend analysis, which allows an objective assessment of the current changes. The article emphasizes the importance of the analysis of the birth rate for the study of various demographic processes in the country, and also provides an overview of the development of this indicator in Russia.